PENGARUH SENAM KEGEL TERHADAP FREKUENSI INKONTINENSIA URINE PADA LANJUT USIA - Ruswati Ruswati (Jurnal Ilmiah Kedokteran dan Kesehatan, 2022)
Urinary incontinence is a micturition disorder in which urine is released uncontrollably and is found in geriatric patients. Data on the prevalence of urinary incontinence in Indonesia was obtained in 2018 at 30%. There needs to be an intervention carried out, namely kegel exercises to control the bladder. The purpose of this literature review is to analyse journals about the effect of kegel exercises on urinary incontinence in the elderly. The elderly from the age of 60 years and over experience psychological changes, one of which is changes in the urinary system which results in urinary incontinence. The cause of urinary incontinence is an increase in the frequency of micturition. To reduce the frequency of micturition by doing kegel exercises to the maximum. The research method used for literature review is through searching journal databases such as google scholar and mendeley (2016-2022) with the keywords kegel exercises, urinary incontinence and elderly so that 6 journals are reviewed, using a one group pretest and posttest study design with inclusion criteria using the PICOS format. The results and analysis of the study based on the results of literature review from 6 journals there is a significant effect between before and after kegel exercises on the frequency of urinary incontinence in the elderly. The result is that after kegel exercises will have an effect on reducing the frequency of micturition, this is because it can tighten the pelvic floor muscles that can withstand micturition. It can be concluded that there is an effect of kegel exercises on the frequency of urinary incontinence in the elderly which is done regularly to strengthen the pelvic muscles, the frequency of micturition decreases. It is expected that the elderly will remain disciplined in doing Kegel exercises, especially those who experience urinary incontinence.